Sindrom Stevens-Johnson (SSJ) melebihi Nekrolisis Epidermal Toksik (NET) pada Geriatri: Laporan kasus - Aliezsa Esthi Kusuma; Dwi Indria Angraini (Medula, 2020)
Steven Johnson Syndrome (SSJ) is an acute, life-threatening disease characterized by necrosis and epidermal release in vesicobulosa skin, mucous orifice, and eyes, with severe general symptoms. The incidence of SSJ overlapping Toxic Epidermal Necrolysis (NET) is 1-10 cases per 1 million cases per year. The most common cause is hypersensitivity reactions to drugs. Pathogenesis of SSJ and NET is still not widely known. Symptoms begin with symptoms of prodromal flu like symptoms followed by bullae and epidermolysis. SSJ and NET based on age have been reported not only as risk factors but also associated with increased mortality. A 66-year-old woman presents with rashes, blisters and blisters accompanied by peeling all over her body including the skin, eyes, lips and genitals. Six days before hospital admission the patient had a history of treatment at a first-level health facility in the form of ondansentron, paracetamol, dexamethasone, chlorpheniramine, glyceryl guaiacolate, salbutamol, antacids and ranitidine. On physical examination found about 27% epidermiolisis body with positive sign Nicolsky. SCORTEN calculated on patient 3. Pharmacological treatment given to patients in the form of intravenous and topical antibiotics and steroids.